SOCIO-GEOGRAPHIC REGION ASPECTS OF CONTROL - Дудник, Іван; Борисюк, Оксана (Human Geography Journal, 2015)
The article is based on socio-geographical methods and principles of general management theory served interpretation of key provisions of regional management as a socio-geographical system. Management principles are grounded geographic features as a general rule (requirements) management of social and geographic systems, during which take into account their logical relationship and mutual subordination. Formalized the basic framework of socio-geographical study these problems.